Tarling Hybridity in the Digitalization Arena: Digital Sociology Study of Modern Music Production - Imawan, Khaerudin (JSW (Jurnal Sosiologi Walisongo), 2025)
Tarling music is referred to as a hybrid cultural product, in addition to being based on historical aspects as an art form that has been acculturated, its development cannot be separated from the influence of technology and communication. The shift in the production, distribution, and consumption practices of Tarling music from classical to modern proves the relationship between analog production methods and digital output. This qualitative research uses a constructivist paradigm to answer the question of how Tarling music as a hybrid cultural product is viewed in the context of global concerns about the interaction of social agents in the digitalization arena. The analysis was conducted based on Deborah Lupton's digital sociology study, supported by Pierre Bourdieu's analysis of the cultural production arena. As a result, through the role of producer agents, managers, and singers, Tarling music revolutionizes itself from analog to digital with the presence of digital music files. The performance of interaction agents with the cyber ecosystem in the digitalization arena to produce, distribute, and consume music through digital platforms.